Methylated tirilazad may mitigate oligofructose-induced laminitis in horses - Tuniyazi, Maimaiti; Tang, Ruibo; Hu, Xiaoyu; Zhang, Naisheng (Frontiers in Microbiology, 2024)
Laminitis is a serious health condition that can cause severe pain and lameness in horses. Due to lack of understanding of laminitis, treatments often fail to achieve the desired results. In recent years, we have begun to recognize that laminitis may involve a complex interaction between local and systemic inflammation.Dysbiosis of the gut microbiota has been linked in the development of systemic inflammation, and our previous findings suggest that the development of laminitis is closely linked to the production of harmful metabolites of the gut microbiota. In addition, it was found that localized lesions in the hoof, especially lamellar injuries, are the most direct cause of laminitis. Matrix metalloproteinases have been found to be strongly associated with the development of laminitis. Recent discovery has found that methylated tirilazad has a role in repairing laminar tissue in vitro. However, its efficacy in horses never has been studied. Therefore, we aimed to investigate the efficacy of methylated tirilazad (product name: PTP-102) in the prevention/treatment of oligofructose-induced laminitis. The results showed that oligofructose successfully induced laminitis in horses, resulting in detreated clinical signs. Blood indices (including inflammation-related indices and other related indices) were significantly increased. Observations of dissection and staining showed significant bleeding, swelling, and damage to hoof tissue. Analysis of the gut microbiota showed a significant decrease in abundance and diversity, and a significant increase in the relative abundance of specific bacteria.Following methylated tirilazad intervention, there were a significant improvement in clinical signs, blood markers and lamellar tissue damage. Additionally, methylated tirilazad positively influenced the gut microbiota structure by reducing the relative abundance of genera closely associated with the development of equine laminitis. This suggests that some of the therapeutic mechanism of methylated tirilazad may be linked to its effects on the gut microbiota. Notably, methylated tirilazad had better effect in the Treatment group than the Prophylactic group, indicating the post-diagnosis utility of methylated tirilazad for laminitis management.